Java, Java, Java Object-Oriented Problem Solving - Morelli, Ralph; Walde, Ralph (Open textbook library., 2016)
We have designed this third edition of Java, Java, Java to be suitable for a typical Introduction to Computer Science (CS1) course or for a slightly more advanced Java as a Second Language course. This edition retains the “objects first” approach to programming and problem solving that was characteristic of the first two editions. Throughout the text we emphasize careful coverage of Java language features, introductory programming concepts, and object-oriented design principles. The third edition retains many of the features of the first two editions, including: Early Introduction of Objects Emphasis on Object Oriented Design (OOD) Unified Modeling Language (UML) Diagrams Self-study Exercises with Answers Programming, Debugging, and Design Tips. From the Java Library Sections Object-Oriented Design Sections End-of-Chapter Exercises Companion Web Site, with Power Points and other Resources The In the Laboratory sections from the first two editions have been moved onto the book's Companion Web Site. Table 1 shows the Table of Contents for the third edition.